Low-temperature annealed methylammonium-free perovskites prepared under ambient conditions in C electrode-based perovskite solar cells. (25th January 2022) - Bidikoudi, Maria; Dracopoulos, Vassilios; Stathatos, Elias
Abstract : A study of the optimization of methylammonium (MA) free perovskite compositions, targeted for their application in hole transport layer (HTL) free perovskite solar cells with a carbon electrode (C-PSCs), is presented. Abstract : A study of the optimization of methylammonium (MA) free perovskite compositions, targeted for their application in hole transport layer (HTL) free perovskite solar cells with a carbon electrode (C-PSCs), is presented. Initially, through the evaluation of cesium and rubidium inorganic cations or mixtures of them used to stabilize the formamidinium (FA) based FAPbI3 perovskite to the black, active phase, cesium (Cs) has emerged as highly promising. Further optimization of the perovskite composition by fine-tuning the Cs/FA ratio has enabled C-PSCs with power conversion efficiencies (PCE) exceeding 12%. The C-PSCs present high photocurrent density and FF values, owing to the optimal crystallization, absorption ability and charge transfer properties, which have been confirmed using spectroscopy methods. Moreover, MA-free C-PSCs have been prepared entirely under ambient conditions, using low cost and low perovskite annealing methods, highlighting the potential of FA based perovskites for large area applications and contributing to the path towards their commercialization.